COMPARISON OF PERFORMANCE OF THREE TYPES OF CATALYSTS OF METHANOL DEHYDRATION TO DME - Siti Masluhah, Via
COMPARISON OF PERFORMANCE OF THREE TYPES OF CATALYSTS OF METHANOL DEHYDRATION TO DME By: Via Siti Masluhah NIM: 23017032 (Master’s Program in Chemical Engineering) The 2017 General Plan of Energy National in Indonesia (RUEN 2017) states that DME will be used as LPG mixing material. This mixing is expected to reduce Indonesia's LPG imports. DME can be used as a substitute for LPG because it is classified as an environmentally friendly fuel and can be produced from various energy resources such as natural gas, coal, and biomass. In general, DME synthesis can be carried out through two types of processes, namely direct processes (one stage) from synthesis gas and indirect processes (two stages) through methanol synthesis and methanol dehydration. This research is part of the development of the Biomass Synthesis System to Fuel. The objective of this research was to test the activity of three types of catalysts for methanol dehydration to DME. The stages of the research included catalyst characterization and catalyst activity testing in the process of dehydration of methanol with temperature variations of 240, 260, and 280oC and WHSV variations of 0,4, 1,2, and 2 h-1. The catalysts used include ?-Al2O3 and two commercial catalysts from the DME plant in Indonesia. This activity test was carried out using methanol feed with a composition of 17-50 mol% in N2 gas and carried out in a fixed bed reactor with a fixed catalyst weight of 2 grams. The characterization results show that the catalysts have a surface area (m2/gram): 194,4 (?-Al2O3), 128,3 (JH202), 370,9 (KADH5) and the acidity (mmol/g.cat): 0,421 (?-Al2O3), 0,308 (JH202), 0,203 (KADH5). In the catalyst activity test, the highest conversion was obtained on the KADH5 catalyst (91%) at a temperetaure of 240oC, while the conversion of methanol with ?-Al2O3 catalyst reached 70,9% at 280oC. The methanol conversion of ?-Al2O3 catalyst is under the thermodynamic equilibrium conversion (90,4%). This study also showed that on the ?-Al2O3 catalyst, a low WHSV (0,4 h-1) resulted a high methanol conversion (84%).